Accounting Profit and Taxable Profit: Shall Never the Twain Meet? - KHOO, Teng Aun (Institutional Knowledge at Singapore Management University, 2012)
The profitability of a company is important for both the company and the tax authority as both need to know the economic result of the company. However accounting income and taxable income are computed differently as they serve different purposes. Profitablity is used to guide the company in deciding whether the business is viable, whereas it is used by the tax authority to determine how much tax is to be levied on the company.